Neutralization of CD95 ligand protects the liver against ischemia-reperfusion injury and prevents acute liver failure - Saeedi, Mohammed al; Steinebrunner, Niels; Kudsi, Hassan; Halama, Niels; Mogler, Carolin; Büchler, Markus W.; Krammer, Peter H.; Schemmer, Peter; Müller, Martina (Cell death & disease, 2018)
Ischemia-reperfusion injury is a common pathological process in liver surgery and transplantation, and has considerable impact on the patient outcome and survival. Death receptors are important mediators of ischemia-reperfusion injury, notably the signaling pathways of the death receptor CD95 (Apo-1/Fas) and its corresponding ligand CD95L. This study investigates, for the first time, whether the inhibition of CD95L protects the liver against ischemia-reperfusion injury. Warm ischemia was induced in the median and left liver lobes of C57BL/6 mice for 45 min. CD95Fc, a specific inhibitor of CD95L, was applied prior to ischemia. Hepatic injury was assessed via consecutive measurements of liver serum enzymes, histopathological assessment of apoptosis and necrosis and caspase assays at 3, 6, 12, 18 and 24 h after reperfusion. Serum levels of liver enzymes, as well as characteristic histopathological changes and caspase assays indicated pronounced features of apoptotic and necrotic liver damage 12 and 24 h after ischemia-reperfusion injury. Animals treated with the CD95L-blocker CD95Fc, exhibited a significant reduction in the level of serum liver enzymes and showed both decreased histopathological signs of parenchymal damage and decreased caspase activation. This study demonstrates that inhibition of CD95L with the CD95L-blocker CD95Fc, is effective in protecting mice from liver failure due to ischemia-reperfusion injury of the liver. CD95Fc could therefore emerge as a new pharmacological therapy for liver resection, transplantation surgery and acute liver failure.
Gesehen am 07.05.2020